Impact of Environmental Degradation on Human Health - Archana, _______; Datta, Charu; Tiwari, Pratibha (International Research Journal of Management, IT & Social Sciences, 2016)
Degradation of environment is one of the most serious challenges before the mankind in todayâs world. Mankind has been facing a wide range of problem arising out of the degradation of environment. Not only the areas under human inhabitation, but the areas of the planet without human population have also been suffering from these problems. As the population increase day by day, the amenities are not improved simultaneously. With the advancement of science and technologies the needs of human beings has been changing rapidly. As a result different types of environmental problems have been rising. Environmental degradation is a wide- reaching problem and it is likely to influence the health of human population is great. It may be defined the deterioration of the environment through depletion of resources such as air, water, and soil. The destruction of ecosystem and extinction of wildlife. Environmental degradation has occurred due to the recent activities in the field of socio-economic, institute and technology. Poverty still remains a problem as the root of several environmental problems to create awareness among the people about the ill effect of environmental pollution. In the whole research it is clear that all factors of environmental degradation may be reduced through- Framing the new laws on environmental degradation, Environment friend policy, Controlling all the ways and means of noise, air, soil and water pollution, Through growing more and more trees and by adapting the proper sanitation policy.Â Â